Descriptors for tree tomato (Solanum betaceum Cav.) and wild relatives - Bioversity International; Instituto de Conservacion y Mejora de la Agrodiversidad Valenciana; Universidad Tecnica Particular de Loja (Bioversity International, 2013)
This work aims to enhance the use and conservation of plant genetic resources and is expected will contribute to studies focusing on the analysis of genetic diversity, germplasm management, definition of new varieties and useful traits for crop improvement.